A Study On The Physical And Mechanical Properties Of Asphaltic Concrete Incorporating Crumb Rubber Produced Through Dry Process [TA443.A7 A136 2007 f rb]. - MOHAMED, ABDULLAHI ALI (2007)
Bitumen konvensional digunakan dengan meluas di kebanyakan negara di mana pada peringkat awal semasa kerja-kerja penghasilan, pembancuhan dan penggunaannya adalah agak sukar. Conventional bitumen is widely used in most countries where it hardens at the early stages during handling, mixing and in service. The level of performance of service life has a close relationship with the properties of bitumen used in the sphaltic concrete.